Characterization of the basic helix–loop–helix gene family and its tissue-differential expression in response to salt stress in poplar - Kai Zhao; Shuxuan Li; Wenjing Yao; Boru Zhou; Renhua Li; Tingbo Jiang (PeerJ, 2018)
The basic helix–loop–helix (bHLH) transcription factor gene family is one of the largest gene families and extensively involved in plant growth, development, and stress responses. However, limited studies are available on the gene family in poplar. In this study, we focused on 202 bHLH genes, exploring their DNA and protein sequences and physicochemical properties. According to their protein sequence similarities, we classified the genes into 25 groups with specific motif structures. In order to explore their expressions, we performed gene expression profiling using RNA-Seq and identified 19 genes that display tissue-differential expression patterns without treatment. Furthermore, we also performed gene expression profiling under salt stress. We found 74 differentially expressed genes (DEGs), which are responsive to the treatment. A total of 18 of the 19 genes correspond well to the DEGs. We validated the results using reverse transcription quantitative real-time PCR. This study lays the foundation for future studies on gene cloning, transgenes, and biological mechanisms.